Parafia i kościół w Zemborzycach w XVIII-XIX wieku - Hamryszczak, Artur; Mącik, Hubert (Archiwa, Biblioteki i Muzea Kościelne, 2016)
The origins of the parish in Zemborzyce, which was probably created soon after the foundation of the village, dates back to the beginning of the 15th century. In 1748, the parish of Zemborzyce consisted of six villages: Zemborzyce, Krężnica (a branch), Trzeszkowice, Osmolice, Prawiedniki and Żabia Wola. It was inhabited by approximately 2,000 faithful. In the parish there was a hospital, which was located in an old building. The parish endowment included arable land, a garden, the right to fish on the River Bystrzyca, a brewery and a taberna with propination laws. In 1779, a new presbytery was built. The outbuildings included: a farm house, a granary, a stable, a cowshed, a barn, a shed for oxen, small stables and pigsties. At the church square there was also a building for an organist. In 1784, a new hospital was built. In 1849, the buildings at the church, apart from the presbytery, included: a servants' house, a curate’s house, a hospital, an inn and the following outbuildings: a stable, a coach house, a granary, a cowshed and a spacious barn. None of these buildings has survived until the present day. The wooden church of Zemborzyce was built in 1717, in place of the previous one. It was renovated several times. It was located to the east of the present church, at the former main road through the village, running over the River Bystrzyca. After constructing the brick church, which exists today, the old church was moved to Motycze near Lublin in 1918. The neo-Gothic brick church, which survived to the present day, was built in 1906-1907. It was designed by the architect of Radom, Augusta Załuski.